Answer:
multiply equation (1) by 3 and equation (2) by 4
Explanations:
The system of equations is:
-4x + 3y = - 11...........(1)
3x - 2y = 8..............(2)
To make one of the variables to be eliminated on addition of the two equations, multiply equation (1) by 3 and equation (2) by 4
3 [ -4x + 3y ] = 3 (-11)
-12x + 9y = - 33.........(3)
4[3x - 2y ] = 4(8)
12x - 8y = 32................(4)
Adding eqaution (3) and (4)
y = -1
Substitute y = -1 into equation (2)
3x - 2(-1) = 8
3x + 2 = 8
3x = 8 - 2
3x = 6
x = 6 / 3
x = 2